2022
DOI: 10.3390/coatings12020127
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Pickling Treatment Parameters on the Surface State and Pre-Passivation Behavior of Super 13Cr Martensitic Stainless Steel

Abstract: As a pre-treatment process in the pre-passivation of stainless steel, pickling treatment has a significant effect on the formation of the pre-passivation film. Thus, the surface composition and defects of Super 13Cr martensitic stainless steel (Super 13Cr) were evaluated under different pickling parameters to further improve the corrosion resistance of the pre-passivation film. The samples were prepared using the acid immersion method and by changing the immersion duration and the acid concentration. The inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 39 publications
0
0
0
Order By: Relevance
“…In this technique, metal substrate surface pre-treatment is recommended prior to the electroplating process. The surface pre-treatment is usually associated with sandpaper polishing, cleaning, pickling, activation, or passivation to prepare the material for plating [9]. It is reported that surface pre-treatment could improve the wettability of the surface, which allowed for a better cohesion of the coating layer and ensured a homogeneous coating [10].…”
Section: Introductionmentioning
confidence: 99%
“…In this technique, metal substrate surface pre-treatment is recommended prior to the electroplating process. The surface pre-treatment is usually associated with sandpaper polishing, cleaning, pickling, activation, or passivation to prepare the material for plating [9]. It is reported that surface pre-treatment could improve the wettability of the surface, which allowed for a better cohesion of the coating layer and ensured a homogeneous coating [10].…”
Section: Introductionmentioning
confidence: 99%